HAKIKAT TUJUAN PENDIDIKAN ISLAM - Azhar Ayu Budiahwati; Mukhlisin; Mohammad Thoriq Aqil Fauzi (Dar El-Falah, 2023)
The nature of the goals of Islamic education is the core of the goals ofislamic education which are defined based on the basic concepts of humans,nature and science and their basic principles. The purpose of education is toproduce human beings who have noble character, are of high quality, havegood morals, and encourage an understanding of life. In addition, the maingoal of islamic education training of the soul, spirituality and senses to leadto goodness, achieve perfection of life and deserve to be caliph fil ardh and‘abdu Allah.